The introduction of sustainability into competitive design network (CDN) - Lambert, Joanna Louise (Cranfield University, 2002)
Competitive Design Network International (CDN) a design consultancy based in Barcelona, Spain is considering the move towards making their business processes more sustainable. This concept was initiated with the encouragement of Cranfield University, by the realisation of Antoni Flores the CEO, and Menno Marien the head of the Innovation department. This study was conducted to discover firstly if and why CDN would want to introduce sustainability, how it could be effectively brought into their practices and what action CDN would need to take. At the close of the project CDN had decided that sustainability would be an important aspect for their business particularly for competitively and market differentiation. CDN being an innovative, adaptable and influential business, it was identified that they are in an advantageous position to do this. Through continuous researcher involvement in the company, a process of education and discussion was initiated. The observations from involvement in the Flores Valles furniture project will be presented, among other implementation issues. The reactions from CDN to the internal seminars carried out will be described and conclusions will be drawn out for other design consultancies.